Extensively Drug Resistant Tuberculosis (XDR-TB) - Lutfor, Afzalunnessa Binte (Bangladesh Journal of Medical Microbiology, 2009)
doi: 10.3329/bjmm.v3i1.2962 Bangladesh J Med Microbiol 2009; 03 (01): 1-3